Strategic plan 2005-2015 (ECLAC SantiagoCL, 2007)
Seeks to guide the activities of the Statistical Conference of the Americas of the Economic Commission for Latin America and the Caribbean (ECLAC) in support of the development of official statistics in Latin America and the Caribbean in accordance with the objectives established in United Nations Economic and Social Council resolution 2000/7 of 25 July 2000.
Keywords: STATISTICAL SERVICES